2017
DOI: 10.17583/redimat.2017.2415
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de las actividades propuestas por un libro de texto: el caso de la medida

Abstract: In this paper we study activities proposed by a Elementary Education (6 to 12 years old) math textbook, this textbook belongs to one of the most used publishers in Spain. We conducted a qualitative analysis of measurement activities proposed by the textbook. The analysis is based on a hierarchy of mathematical tasks that allow us to characterize the contents of measurement. Results show a predominance of arithmetical tasks in the activities as they leave in a second term conceptual and procedural aspects of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
2
0
7
Order By: Relevance
“…That gives cause for concern, for as the NCTM [36] notes, "it is unlikely that children can gain a deep understanding of measurement without handling materials, making comparisons physically, and measuring with tools" (p. 44). The skills required are in fact more closely related to understanding and operating with the decimal system than to measurement per se [27]. These elements are cited in Royal Decree 126/2014 [14] under the unit for teaching measurement, while assessment criterion 4 for measurement specifies that students must be able "to use the most common units of measure, convert one unit into others within a given magnitude, express the results in the most suitable unit, explain the procedure followed both orally and in writing and apply it to solve the problem" (p. 19391).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That gives cause for concern, for as the NCTM [36] notes, "it is unlikely that children can gain a deep understanding of measurement without handling materials, making comparisons physically, and measuring with tools" (p. 44). The skills required are in fact more closely related to understanding and operating with the decimal system than to measurement per se [27]. These elements are cited in Royal Decree 126/2014 [14] under the unit for teaching measurement, while assessment criterion 4 for measurement specifies that students must be able "to use the most common units of measure, convert one unit into others within a given magnitude, express the results in the most suitable unit, explain the procedure followed both orally and in writing and apply it to solve the problem" (p. 19391).…”
Section: Discussionmentioning
confidence: 99%
“…Textbook analysis and comparison is a line of research widely explored in mathematics [25] and science [26] teaching, due to their high application in the classroom. One particularly prominent study in connection with measurement by Mengual et al [27] analysed publisher Vicens Vives's primary school mathematics books. The authors found that measurement was the priority activity in the lower 2 years, followed by measurement comparison and sorting, whereas in the upper 4 years the focus was on converting units, geometric measurement and word problems involving measurements.…”
Section: Textbook Analysismentioning
confidence: 99%
“…Puesto que dicha noción sí está presente en los libros de texto como veremos más adelante, queda justificado su estudio. Mengual et al (2017), en la misma línea anterior, consideran el currículo potencial determinado por las diversas publicaciones docentes y materiales, entre ellos los libros de texto, desarrollando el currículo oficial desde un punto de vista teórico y práctico.…”
Section: Análisis De Libros De Textounclassified
“…Estos se han realizado desde diferentes enfoques teóricos como el análisis didáctico (Picado et al, 2013y Real et al, 2013, el ontosemiótico (Ake y Godino, 2018;Balcaza et al, 2017;Sánchez y Ramírez, 2018); desde la visualización (Barrantes et al, 2015); o bien, desde la socioepistemología (Cantoral et al, 2015). En otros (López et al, 2015;Mengual et al, 2017;Moreno et al, 2007;Sánchez y Ruíz, 2018;Vicente y Manchado, 2017) se construyen categorías para analizar tareas o problemas planteados en los libros.…”
Section: Pna 14(4)unclassified